Design of multipurpose table based on anthropometric data / Nur Athirah Mohd Adzha - Mohd Adzha, Nur Athirah (Faculty of Applied Sciences, 2015)
This study was conducted to analyze the existing anthropometric data to make the functional design of the multipurpose table. The multipurpose table was choose due to the current issue, which are small space of the room and not suitable for the space. The raw material for the multipurpose table is blackboard, because the blockboard easy to get and light in weight. In addition, the anthropometric data take from the previous student thesis in furniture (bachelor) and it is consists 13 physical dimensions. The anthropometric data between male and female students was analyzed to get the average dimensions to make the multipurpose table. Furthermore, in the study, anthropometric data for male students is higher than the female students. The anthropometric data is very important to make the furniture because people have difference size and shape, therefore the furniture cannot be produce without refer to the anthropometric data. After that, the selection of the physical dimensions of the anthropometric data also is very important to make the furniture. This is because, when the selection of the physical dimensions is wrong. so the dimensions of the furniture also will be wrong.